Electron Densities in H ii Regions from Observation of [N ii] 205 μm Fine Structure and Radio Recombination Lines - Goldsmith, Paul. F.; Anderson, L. D.; Pineda, Jorge L.; Aladro, Rebeca; Ricken, Oliver (The Astrophysical journal, 2024)
We employ observations of the 205 μ m [N ii ] fine structure (FS) line and radio recombination line (RRL) emission to derive the electron density in 10 well-known H ii regions. The combination of these two spectral lines (the RRL–FS line method) provides a sensitive probe of electron density in regions with n (e) ≥ 30 cm −3 without requiring knowledge of the size of the ionized region. By using H54 α data from the Green Bank Telescope and 205 μ m data from the SOFIA Airborne Observatory, we have almost identical 18″ beamwidths, removing a significant source of error for observations of H ii regions due to nonuniform density across the sources observed. The electron densities vary widely among the sources observed, from 2600 to 36,000 cm −3 , with two low-density outliers at 94 and 520 cm −3 . On average, these densities are a factor of 4 greater than the highest-resolution single-antenna data and a factor of almost 13 greater than the 182″ angular resolution single-antenna data having more sources in common. The total 1 σ fractional uncertainties in n (e) are in the range 0.15–0.29. In the RRL–FS line method, the observationally determined quantity is proportional to ∫ n 2 ( z ) dz / ∫ n ( z ) dz . For a Gaussian density distribution much more extended than its 1/ e radius, this is equal to n 0 / 2 , where n 0 is the peak electron density. The high values of electron density found are plausibly the result of the RRL–FS line technique sampling the peak of a centrally condensed density distribution.